2012
DOI: 10.1371/journal.pone.0040273
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perinatal Dioxin Exposure on Infant Growth: A Cross-Sectional and Longitudinal Studies in Dioxin-Contaminated Areas in Vietnam

Abstract: Dioxin exposure levels remain elevated in residents living around former US Air Force bases in Vietnam, indicating potential adverse impacts on infant growth. In this study, 210 mother–infant pairs in dioxin-contaminated areas in Vietnam were recruited at the infants’ birth and followed up for 4 months. Perinatal dioxin exposure levels were estimated by measurement of polychlorinated dibenzo-p-dioxins/furans toxic equivalent (PCDDs/Fs-TEQ) in breast milk. The infants’ size was measured at birth and 1 and 4 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 36 publications
8
27
0
1
Order By: Relevance
“…Infant boys born in these regions show subtle deficits in growth rates, neurodevelopmental measures at 4 months and motor and language deficits at 3 years (Nishijo et al, 2014;Nishijo et al, 2012), consistent with the subtle morphological, motor, and cognitive deficits found during early childhood in schizophrenia (Reichenberg et al, 2010) and the genetic overlap between autism and schizophrenia (Stefansson et al, 2014). Interestingly,…”
Section: Aryl Hydrocarbon Receptor Signalingsupporting
confidence: 62%
“…Infant boys born in these regions show subtle deficits in growth rates, neurodevelopmental measures at 4 months and motor and language deficits at 3 years (Nishijo et al, 2014;Nishijo et al, 2012), consistent with the subtle morphological, motor, and cognitive deficits found during early childhood in schizophrenia (Reichenberg et al, 2010) and the genetic overlap between autism and schizophrenia (Stefansson et al, 2014). Interestingly,…”
Section: Aryl Hydrocarbon Receptor Signalingsupporting
confidence: 62%
“…Previously, our study of the same cohort indicated that boys were more susceptible to the neurotoxic effects of dioxin exposure (as indicated by the levels of PCDDs/Fs-TEQ), with lower neurodevelopment scores observed across all three domains among the high-exposed boys (⩾75 percentile of all participants). 13 Our present results among 3-year-olds showed a clear negative effect of high-PCDDs/Fs-TEQ exposure on the cognitive, language and motor functioning of boys. A study of the Yusho patients, whose mothers were accidentally exposed to rice oil contaminated with PCDDs/Fs and PCB, demonstrated that males were more susceptible to growth restriction than females.…”
Section: Validity Of Dioxin Effectssupporting
confidence: 51%
“…11,12 We recently reported the substantial effects of perinatal dioxin exposure on the neurodevelopment of 4-month-old infants living in areas of Vietnam that had been contaminated by Agent Orange and other herbicides during the Vietnam War from 1961 to 1971. 13,14 The levels of TCDD and PCDDs/Fs in the breast milk of mothers were three to four times higher than those of mothers living in unsprayed areas. 15 Moreover, we found that the presence of several furan isomers in breast milk was correlated with test scores of social -emotional behavior and attention in our preliminary survey of 3-year-old children from a highly polluted area around a former airbase in the same region.…”
Section: Introductionmentioning
confidence: 98%
“…Previous reports have provided evidence that perinatal dioxin exposure to 2,3,7,8-TetraCDD and PCDDs/Fs-TEQ in the breast milk and postnatal dioxin load indicated by the infant daily dioxin intake (DDI) were inversely associated with infant neurodevelopment. At 4 months, dioxin exposure predominantly affected cognitive and fine motor skills of these infants Nishijo et al, 2012). The results of neurodevelopmental examination at 3 years of age provided evidence that total dioxin exposure, as indicated by PCDDs/Fs-TEQ levels, primarily affected the cognitive, language, and motor function of 3-year-old boys.…”
Section: Introductionmentioning
confidence: 88%